Air pollution nanoparticle and alpha-synuclein fibrils synergistically decrease glutamate receptor A1, depending upon nPM batch activity - Hongqiao Zhang; Carla D'Agostino; Christopher Tulisiak; Max A. Thorwald; Liza Bergkvist; Allison Lindquist; Lindsay Meyerdirk; Emily Schulz; Katelyn Becker; Jennifer A. Steiner; Mafalda Cacciottolo; Mohit Kwatra; et al. (Heliyon, 2023)
Background: Epidemiological studies have variably linked air pollution to increased risk of Parkinson’s disease (PD). However, there is little experimental evidence for this association. Alpha-synuclein (α-syn) propagation plays central roles in PD and glutamate receptor A1 (GluA1) is involved in memory and olfaction function. Methods: Each mouse was exposed to one of three different batches of nano-particulate matter (nPM) (300 μg/m3, 5 h/d, 3 d/week), collected at different dates, 2017–2019, in the same urban site. After these experiments, these nPM batches were found to vary in activity. C57BL/6 female mice (3 mo) were injected with pre-formed murine α-synuclein fibrils (PFFs) (0.4 μg), which act as seeds for α-syn aggregation. Two exposure paradigms were used: in Paradigm 1, PFFs were injected into olfactory bulb (OB) prior to 4-week nPM (Batch 5b) exposure and in Paradigm 2, PFFs were injected at 4th week during 10-week nPM exposure (Batches 7 and 9). α-syn pSer129, microglia Iba1, inflammatory cytokines, and Gria1 expression were measured by immunohistochemistry or qPCR assays. Results: As expected, α-syn pSer129 was detected in ipsilateral OB, anterior olfactory nucleus, amygdala and piriform cortex. One of the three batches of nPM caused a trend for elevated α-syn pSer129 in Paradigm 1, but two other batches showed no effect in Paradigm 2. However, the combination of nPM and PFF significantly decreased Gria1 mRNA in both the ipsi- and contra-lateral OB and frontal cortex for the most active two nPM batches. Neither nPM nor PFFs alone induced responses of microglia Iba1 and expression of Gria1 in the OB and cortex. Conclusion: Exposures to ambient nPM had weak effect on α-syn propagation in the brain in current experimental paradigms; however, nPM and α-syn synergistically downregulated the expression of Gria1 in both OB and cortex.